(untitled) (Research, Society and Development, 2021)
This study developed a software that calculates the chance of the health professional having zero, one, two, three or four or more accidents with biological hazards. Data from 111 questionnaires of health workers in primary and emergency care were used. The program achieved 95% accuracy in the training set (n=88) and 74% in the test set (n=23). The statistically significant associations, which also relied on data from 1,094 work accident reports, were greater abandonment of follow-up by physicians after an accident with biological materials in comparison with other professionals (p=0.02), nursing technicians and a higher prevalence of accidents with biological materials than other professionals (p<0.001), emergency care workers have more accidents with biological materials than primary care professionals (p<0.001) and increased follow-up abandonment after an accident with biological materials in the 2016-2018 period compared to 2007-2009 (p<0.001).